The Educational Implications Deduced from the Meccan Forty Hadiths and Their Applications in the Meccan Society – A Field Study on the Workers in the Project of Venerating the Sacred Land - Alhebi, Faris Abdullah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to state the educational importance of the forty Meccan Hadith’s, to monitor the educational dimensions that included the forty Hadiths about virtue of Makkah, to Clarify the educational implementations that was elicited of Contents of the forty Meccan Hadiths with their reflections in the Meccan society, to identify whether there are any significant statistical differences in the perceptions of the workers in the project to glorify the sacred city in contrast, the educational importance of the forty Meccan Hadiths, their educational implementations as well as, their practical applicable dimensions in Meccan society. The researcher used descriptive, analytical and survey methods of research on a sample of the study. A group of 80respondents who were working and cooperating with the glorification of the Sacred City - in Makkah Al-Mukarramah. The study concluded: 1. The glorification of God’s rituals in Makkah Al-Mukarramah is entrusted and commanded by the law of Sharia. 2. That the historical status of the mountains of Makkah Al-Mukarramah and the places that are associated with the Prophet’s biography. Has a huge influential value and a great impact of awe and glorification. Having a sense of impact on the souls of its inhabitants and visitors. 3.The unity and glorification of God the Almighty is the greatest educational significance of Hajj and its rituals. 4. The educational contents extrapolated from the Forty Meccan Hadiths has a significant impact in disciplining adults and raising children to no violate the sanctity of Mecca. 5. Leaving Makkah and residing in other place as an asceticism and if without necessity from the abominations. The duty is rather to entice people to stay in Makkah even if the person encountered difficulty living there. 6. Providing education to all residents, pilgrims, Umrah performers, and visitors is a necessity. It’s a necessity for veneration, reverence, glorification, obedience, and to emulate the guidance of the Prophet peace be upon him. 7. The educational principles derived from the Qur’an and the teachings of the Prophet, aimed at honoring the Sacred Land of God, constitute a valuable resource that should be recognized and endorsed by different institutions as a curriculum. It is crucial to disseminate this material among the members of the Meccan community, encompassing residents, workers, and visitors alike.